2017
DOI: 10.1007/s10681-017-1939-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis for lodging tolerance and plant height in a diverse European hexaploid oat collection

Abstract: Sensitivity to lodging of oat varieties has been reduced in the last decades through the introduction of dwarfing genes. However, lodging may still cause significant yield loss, underscoring the need for new oat varieties with higher levels of lodging tolerance. In the present study, we analysed lodging and plant height in a collection of European oat accessions including landraces, old and modern varieties, in order to perform a genome-wide association study (GWAS) for identifying markers associated to lodgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
2
27
1
Order By: Relevance
“…For the plant height the check mean was 98 cm, which was surpassed by 130 out of the entire 260 accessions in the collection, and turned to be too tall for the target environments. The variation in plant height (i.e., 68 to 149 cm; Table 1) was similar to the values reported for a European hexaploid oat collection screened within the AVEQ project [45]. Plant height is associated with lodging, but many other aspects also the affect lodging of oats [46].…”
Section: Quantitative Genetic Parameters and Trait Correlationssupporting
confidence: 76%
See 2 more Smart Citations
“…For the plant height the check mean was 98 cm, which was surpassed by 130 out of the entire 260 accessions in the collection, and turned to be too tall for the target environments. The variation in plant height (i.e., 68 to 149 cm; Table 1) was similar to the values reported for a European hexaploid oat collection screened within the AVEQ project [45]. Plant height is associated with lodging, but many other aspects also the affect lodging of oats [46].…”
Section: Quantitative Genetic Parameters and Trait Correlationssupporting
confidence: 76%
“…Plant height is associated with lodging, but many other aspects also the affect lodging of oats [46]. Therefore, the correlation between plant height and lodging is often only moderate when a large collection of germplasm is screened [45]. In the present study, no correlation between plant height and lodging was observed as the breeders discarded too tall accessions after the first year and environmental conditions did not favor lodging thereafter.…”
Section: Quantitative Genetic Parameters and Trait Correlationsmentioning
confidence: 46%
See 1 more Smart Citation
“…Lodging is the failure of plants to maintain an upright position under unfavourable weather conditions (rain and strong wind) (Tumino et al., ). When lodging occurs in cereals during or just after anthesis, it can cause severe losses in grain yield and reduce grain quality and mechanical harvesting efficiency (Acreche & Slafer, ; Berry & Spink, ; Pendleton, ; Stanca, Jenkins, & Hanson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of GWAS in polyploid species is relatively new, although there have already been a number of studies published in various crop species, for example in potato, oilseed rape, wheat, and oats (Uitdewilligen et al, 2013;Gajardo et al, 2015;Sukumaran et al, 2015;Tumino et al, 2016;Tumino et al, 2017). GWAS studies usually need to account for population structure and relatedness to prevent spurious associations, often in the context of linear mixed models (Yu et al, 2006;Bradbury et al, 2007;Zhang et al, 2010b).…”
Section: Polyploid Gwasmentioning
confidence: 99%